Passively Q-Switched Mode-Locked Tm,Ho:CaYAlO4 Laser Based on Double-Walled Carbon Nanotube Saturable Absorber - Zhang, Yani; Ling, Weijun; Qiao, Dun; Sun, Rui; Chen, Chen (Frontiers in Physics, 2020)
A passively Q-switched mode-locked (QML) operation in Tm,Ho:CaYAlO4 bulk laser was demonstrated experimentally by employing double-walled carbon nanotubes (DWCNTs) as a saturable absorber. The laser is pumped by a self-made wavelength tunable Ti:sapphire laser, and the pump threshold of Tm,Ho:CaYAlO4 laser was measured at 677 mW using transmittance of 1.5% output coupler. A stable QML operation state was achieved when the absorption pumping power reached 1,958 mW. When the pumping power reached 2.6 W, the maximum output power was 64 mw with a central wavelength of 2,085 nm, the corresponding repetition frequency of mode-locked pulse was 98.04 MHz, and the modulation depth in Q-switching envelopes is close to 100%.